2013
DOI: 10.1097/aog.0b013e3182864350
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality Associated With Oophorectomy Compared With Ovarian Conservation in the Nurses' Health Study

Abstract: Objective To report long-term mortality following oophorectomy or ovarian conservation at the time of hysterectomy in subgroups of women based on age at the time of surgery, use of estrogen therapy, presence of risk-factors for CHD and length of follow-up. Methods A prospective cohort study of 30,117 Nurses’ Health Study participants having a hysterectomy for benign disease Multivariable-adjusted hazard ratios [HR] for death from CHD, stroke, breast cancer, epithelial ovarian cancer, lung cancer, colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
228
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(241 citation statements)
references
References 17 publications
5
228
3
5
Order By: Relevance
“…6163 In the Nurse’s Health Study, women who underwent BSO before the age of 50 years had a significant increase in all-cause, total cancer, and cardiovascular mortality over 28 years of follow-up. 3 Similarly, Gierach et al found younger age at BSO to be associated with increased risk of all-cause mortality, and specifically with mortality related to CHD. This risk decreased progressively with increasing age at BSO, disappearing by the age of 50 years.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…6163 In the Nurse’s Health Study, women who underwent BSO before the age of 50 years had a significant increase in all-cause, total cancer, and cardiovascular mortality over 28 years of follow-up. 3 Similarly, Gierach et al found younger age at BSO to be associated with increased risk of all-cause mortality, and specifically with mortality related to CHD. This risk decreased progressively with increasing age at BSO, disappearing by the age of 50 years.…”
Section: Resultsmentioning
confidence: 95%
“…13 Yet, a significant percentage of women still undergo elective BSO at the time of hysterectomy for benign disease (23% of women 40–44 years and 45% of women 45–49 years). 46 …”
Section: Introductionmentioning
confidence: 99%
“…However, results are consistent that bilateral oophorectomy at age younger than 50 is associated with an increased risk of CVDs and CVD mortality (results have been inconclusive for bilateral oophorectomy at age older than 50). [42][43][44] Similarly, hysterectomy without oophorectomy has been shown to be associated with an increased risk of CVD in women aged <50 but not in women aged ≥50. 44 In addition, this finding was consistent with the previous endometriosis and CHD study which found that hysterectomy/oophorectomy and earlier age at these surgeries accounted for 40% of the overall association.…”
Section: Analysis 2: Hypercholesterolemia or Hypertension In Relationmentioning
confidence: 99%
“…The benefits of ovarian preservation for women at average risk have been described up to age 55 and may extend to women of even older age (74, 75). Careful individualization of counselling and treatment must take into account the patient's personal history of cancer, age, wishes regarding fertility and concomitant medical comorbidities, particularly if considering prophylactic surgery.…”
Section: Surgical Prevention For Women At High Risk Of Ovarian Cancermentioning
confidence: 99%